POLA REKRUTMEN POLITIK CALON ANGGOTA LEGISLATIF PEREMPUAN PEMILU 2019 (STUDI PADA DPD PDIP JAWA TENGAH) - Irsyad - Majid; Fitriyah - - (Journal of Politic and Government Studies, 2021)
This research discusses the political recruitment patterns of women candidates of PDIP at the DPRD of Central Java Province. The purpose of this study was to explaine how the recruitment patterns were carried out for female candidates by the PDIP Central Java Board, based on fact the women candidates of PDIP was elected in the largest than other parties. This study used a qualitative method with a case study approach. Data collection was carried out through interviews with two women candidates from PDIP who was elected, the new comer and the incumbent, and one of the PDIP Central Java Board, besides using document as supporting data. The analyzing data used reducing, displaying, and verification. The study results finds the women candidate recruitment model of PDIP Central Java Board in the 2019 election is openness (open for cader and non-cader) at the certification stage, the nomination process was centralized at the National PDIP Board, any special reward point for dedicated cader (through scorring), and gender neutral by same treatment between male and female. The conclusion of this study is that the recruitment pattern of women legislative candidates is carried out directly by the DPD PDIP Central Java administrators based on PDIP Regulation Number 25-A of 2018 concerning Recruitment and Selection of Candidates for Members of DPR, DPD, Provincial and Regency / City DPRD. The final decision also involves the role of the DPP Party. There are priority rights for party officials in candidacy. This study recommends the PDIP to apply affirmative action in the candidacy, but this recommendation requires a more research base, not only from this research whose results cannot be generalized. Due to the limitations of the study in this study, further research is suggested to raise the case of the recruitment of female candidates by PDIP in other regions.